Clinical radiology : the essentials - Daffner, Richard H., 1941- 4 0 16; 5 (Philadelphia, PA : Wolters Kluwer/Lippincott Williams & Wilkins, 2007)
A comprehensive guide to clinical radiology that covers the principles of diagnostic imaging; radiographic contrast agents; interventional and invasive radiology; pulmonary, cardiac, breast, gastrointestinal, urinary tract, obstetric, gynecologic, musculoskeletal, cranial, and vertebral imaging; and abdominal radiographs.
Overview and principles of diagnostic imaging -- Radiographic contrast agents -- Interventional and invasive radiology -- Pulmonary imaging -- Cardiac imaging -- Breast imaging -- Abdominal radiographs -- Gastrointestinal imaging -- Urinary tract imaging -- Obstetric and gynecologic imaging -- Musculoskeletal imaging -- Cranial imaging -- Vertebral imaging.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; methods -- Diagnostic imaging.;Diagnosis, Radioscopic.;Diagnostic Imaging;Diagnostic imaging.;Radioscopic diagnosis. -- Atlases; 20; 2